The new concept of ureteral access sheath with guidewire disengagement: one wire does it all - Breda, Alberto; Knoll, Thomas (World journal of urology, 2016)
Purpose To prospectively evaluate the new Flexor©Parallel™ Rapid Release™ (Cook®, Bloomington, IN, USA) access sheath (UAS) which allows the use of a single wire to serve as both safety and working guide.Materials and methods Between June and September 2014, adult patients from five European centers who underwent flexible ureteroscopy (fURS) for therapeutic and diagnostic purposes were included. The 12/14Fr Flexor©Parallel™ UAS was evaluated. Data were collected and examined by both univariate and multivariate analyses. The UAS material and usage characteristics were rated per case by the surgeons on a scale from very bad to very good.ResultsIn total, 134 UASs were used in 67 male and 67 female patients. Fifty percent of ureters (67 patients) were pre-stented. Ninety percent of the procedures were therapeutic. The overall successful insertion rate was 94 %. Pre-stenting status was the only independent factor for a successful access sheath insertion: 98.5 % of the pre-stented patients had a successful UAS placement vs. 82 % of non-pre-stented (p = 0.001, C.I. 95 %: 1.2). Evaluation of the material and radiopacity was considered very good in over 90 % of cases. Release of the guidewire, hydrophilic coating, gliding of the endoscope and repeatability were considered very good in over 80 %. There were two (1.4 %) UAS malfunctions and one submucosal lesion reported.ConclusionsThe use of the Flexor©Parallel™ Rapid Release™ (Cook®, Bloomington, IN, USA) with usage of a single guidewire in a prospective multicentric scenario was clinically applicable in the majority of cases. Pre-stenting increased the chance of a successful insertion from 82 to 98.5 %.